Architecture for community-based ageing – A shape grammar for transforming typical single-family houses into old people's cohousing - Belčič, A.; Eloy, S. (Buildings, 2023)
In Slovenia, the existing organised housing infrastructure for people over 65 years of age is in-sufficient and lacks diversification. Older people are often homeowners, many of whom dwell in large, underused single-family houses that require adaptations. Some have the potential to be transformed into small co-housing communities of 3–6 older people. The houses in question are mostly pattern-book houses of various types, built in the first decades after WWII. To approach the problem of converting this mass resource while providing enough flexibility for individual customisation, a shape grammar was proposed, with the intension of expanding the range of design variations for the transformation of single-family houses and presenting them to both users and architects for further assessment. The shape grammar was inferred based on a corpus of case studies developed by architecture students across two weeklong workshops. Three general strategies emerged—splitting the house vertically (according to sleeping/private and liv-ing/communal functions), horizontally, or with the maximum number of sleeping/private spaces. Essential spaces were catalogued to determine the conditions and requirements for assigning every transformation rule. The result was a simple, yet versatile composition generator. Through the development of a user-friendly interface, this resource could be used to empower potential inhabitants in the transformation design process.